THE IMPORTANCE OF FOREIGN LANGUAGE LEARNING - Teshaboyeva Nafisa Zubaydulla qizi; Aktamova Farangiz Farrux qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract In the modern globalized world, foreign language learning has become an essential component of education, communication, and professional development. The ability to speak more than one language enhances cognitive abilities, academic achievement, cultural awareness, and career opportunities. This article examines the importance of foreign language learning from cognitive, educational, social, cultural, and professional perspectives. Based on scientific research and international studies, the paper highlights how language learning strengthens mental skills, promotes intercultural understanding, and supports global cooperation. Furthermore, the study emphasizes the role of foreign language education in preparing individuals for the demands of the global labor market and digital communication era. The findings suggest that foreign language learning is not only an academic skill but also a lifelong investment in personal growth and global citizenship.